2020
DOI: 10.1021/acs.molpharmaceut.0c00773
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Efavirenz and HIV-1 Fusion Inhibitor Peptide Co-loaded Polymer–Lipid Hybrid Nanoparticles: Statistical Optimization, Cellular Uptake, and In Vivo Biodistribution

Abstract: The objective of the present study was to develop long-acting efavirenz (Efa)−enfuvirtide (Enf) Co-loaded polymer−lipid hybrid nanoparticles (PLN) with improved intracellular delivery to target T-cells and macrophage cells located in multiple human immunodeficiency virus sanctuaries. The Box−Behnken design was utilized to optimize three high-risk factors, namely, Efa amount, sonication time for primary emulsion, and sonication time for aqueous nanodispersion obtained from preliminary studies. Lyophilized Efa−E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…The dosage form was able to deliver the antiviral payload to infected sites like lymph nodes and the reproductive tract for 5 days. Interestingly, the nanoparticles also permeated the blood-brain barrier and the results were promising to employ nanoformulations for LA delivery in human use [144]. For the delivery of a synergistic two-drug ARV combination consisting of a pre-clinical NNRTI, Compound 55, and NRTI, 4 -ethynyl-2-fluoro-2 -deoxyadenosine (EFdA), Beelor et al developed two LA-ART interventions, one an injectable nano-formulation and the other based on pharmacokinetics and antiviral activity in a hu-mouse model of HIV infection.…”
Section: Formulationmentioning
confidence: 95%
See 1 more Smart Citation
“…The dosage form was able to deliver the antiviral payload to infected sites like lymph nodes and the reproductive tract for 5 days. Interestingly, the nanoparticles also permeated the blood-brain barrier and the results were promising to employ nanoformulations for LA delivery in human use [144]. For the delivery of a synergistic two-drug ARV combination consisting of a pre-clinical NNRTI, Compound 55, and NRTI, 4 -ethynyl-2-fluoro-2 -deoxyadenosine (EFdA), Beelor et al developed two LA-ART interventions, one an injectable nano-formulation and the other based on pharmacokinetics and antiviral activity in a hu-mouse model of HIV infection.…”
Section: Formulationmentioning
confidence: 95%
“…Nevertheless, many NNRTI's as LA formulations are still in the developmental stage with Cabenuva being approved recently and can be expected in the next decade (Table 1). Preclinical Subcutaneous [144] Drug adherence to multiple drugs is essential to prevent relapse, and hence the dosage regimen by extending dosing intervals by LA formulation may lead to a successful therapeutical approach. Recently, ViiV Healthcare and Janssen Pharmaceuticals (Janssen) developed a dosing kit containing separate injectable suspensions of Cabotegravir and RPV for intramuscular (IM) use (Table 2).…”
Section: Formulationmentioning
confidence: 99%
“…Clearly, the extent of therapeutic drug penetration into crucial niches within the GI tract requires further study, as it is critical that any cure option be efficacious in targeting intestinal viral reservoirs. It is encouraging, therefore, that contemporary drug design has focused on ensuring tissue penetration, often including the GI tract, of ARVs and that great strides have been made in ensuring tissue biodistribution [41][42][43].…”
Section: The Gastrointestinal Tract: An Important Compartment For Hiv...mentioning
confidence: 99%
“…A great variety of works are investigating new means and bioengineering techniques to deliver drugs to infected cells and/or present immunogens to immune cells in specific compartments, which could lead to enhanced efficiency of natural immune responses [ 181 , 182 , 183 , 184 , 185 , 186 ]. Pino et al demonstrated in SIV-infected RM that administration of FTY720 (fingolimod), a drug used to treat multiple sclerosis, limits viral persistence by increasing the number of cytolytic cells in the LN, a critical site for HIV/SIV replication and persistence [ 187 ].…”
Section: Evaluation Of Hiv Cure Strategies With the Help Of Nhp Modelsmentioning
confidence: 99%